Pengaruh PDRB Per Kapita, Tingkat Kemiskinan dan Pengeluaran Pemerintah terhadap Indeks Pembangunan Manusia di Provinsi Sumatera Barat - Dea Fahera; Mike Triani (Media Riset Ekonomi Pembangunan (MedREP), 2025)
This study aims to analyze the effect of Gross Regional Domestic Product (GRDP) per capita, poverty rate, and government expenditure on the Human Development Index (HDI) in West Sumatra Province. The study employs panel data from 12 regencies and 7 cities over the period 2020–2024. The analytical method used is panel data regression with the Fixed Effect Model (FEM) approach. The results indicate that GRDP per capita has a positive and significant effect on HDI, the poverty rate has a negative but insignificant effect on HDI, while government expenditure has a positive and significant effect on HDI. Simultaneously, the three variables significantly influence HDI in West Sumatra. These findings emphasize the importance of increasing community income and enhancing the effectiveness of regional budget management to support human development, as well as the need for strategic policies to mitigate the impact of poverty.